Nutritional Management of Renal Disease - Kopple, Joel D. (Elsevier Science, 2013)
This translational text offers in-depth reviews of the metabolic and nutritional disorders that are prevalent in patients with renal disease. Chapter topics address the growing epidemic of obesity and metabolic syndrome. Each chapter integrates basic and clinical approaches, from cell biology and genetics to diagnosis, patient management and treatment. Chapters in sections 4-7 include new illustrative case reports, and all chapters emphasize key concepts with chapter-ending summaries. New features also include the latest National Kidney Foundation Clinical Practice Guidelines on Nutrition in Chronic Renal Failure, the most recent scientific discoveries and the latest techniques for assessing nutritional status in renal disease, and literature reviews on patients who receive continuous veno-venous hemofiltration with or without dialysis.